Food for thought achieving youth consciousness and involvement in agroecology through an immersive learning environment - Valera, Sofia Regina R. (College of Architecture, University of the Philippines Diliman, 2022)
At the heart of the fragile city are the vulnerable Filipino youth heavily bearing the burden of food insecurity. This is affected primarily by environmental, institutional, agricultural, and health and economic pressures, and is exacerbated by the youth's lack of involvement, appreciation, and interest in agriculture. Hence, scholars and the current secretary of the Department of Agriculture acknowledge the significance of the youth stepping up as front liners in food security and nutrition. Despite the implementation of the Technical Vocational track with agriculture-related specializations under the K to 12 program of the Department of Education, the program was met with low satisfaction ratings and low awareness and involvement on career interests in the agricultural field due to the limited resources, lack of relevant work immersion partners and facilities, and other specializations relevant to the needs of the community. This comprehensive design project addresses the inefficiency of youth-centered immersion and learning facilities that supposedly boost attraction and employment in the agriculture sector. There still remains a gap in the literature of designs for educational spaces that are efficient in pushing the youth towards involvement in Agroecology. Having a designated space to bridge this gap would provide and aid the youth in their battle against food insecurity especially during unprecedented times. Providing a stimulating learning environment through the mere-exposure theory, within the context of the agriculture industry from a career development perspective, increases the success rate of education to employment transitions in the same field. This project, by closely examining immersive learning environments, integrating sustainable urban farming methods, and reinventing agriculture-related career recruitment in the K to 12 program sheds light on ways of establishing Agro-Ecological consciousness and involvement amongst the youth.